2011
DOI: 10.1371/journal.pone.0022669
|View full text |Cite
|
Sign up to set email alerts
|

Workflow and Atlas System for Brain-Wide Mapping of Axonal Connectivity in Rat

Abstract: Detailed knowledge about the anatomical organization of axonal connections is important for understanding normal functions of brain systems and disease-related dysfunctions. Such connectivity data are typically generated in neuroanatomical tract-tracing experiments in which specific axonal connections are visualized in histological sections. Since journal publications typically only accommodate restricted data descriptions and example images, literature search is a cumbersome way to retrieve overviews of brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 79 publications
2
44
0
Order By: Relevance
“…The positions of the injection site centers were inferred from histological analyses of anatomical landmarks and cytochrome oxidase staining patterns (Zakiewicz et al, 2011). Inspection of sections stained for cytochrome oxidase revealed that the injections into S1 barrel cortex involved both barrels (D2, D3 or D5) and adjacent septa.…”
Section: Resultsmentioning
confidence: 99%
“…The positions of the injection site centers were inferred from histological analyses of anatomical landmarks and cytochrome oxidase staining patterns (Zakiewicz et al, 2011). Inspection of sections stained for cytochrome oxidase revealed that the injections into S1 barrel cortex involved both barrels (D2, D3 or D5) and adjacent septa.…”
Section: Resultsmentioning
confidence: 99%
“…The rat connectivity component of the rodent brain workbench (Zakiewicz et al, 2011), providing public access to raw tract-tracing images, registered to a common atlas space.…”
Section: Introductionmentioning
confidence: 99%
“…But despite the numerous connectivity studies conducted through many decades we are still far from achieving comprehensive descriptions of the connectome across all these levels. There is increasing awareness that new neuroinformatics tools and strategies are needed to achieve the goal of compiling the brain's connectome, and that any such effort will require systematic, large-scale approaches (Bohland et al, 2009;Akil et al, 2011;Zakiewicz et al, 2011;Van Essen and Ugurbil, 2012).…”
Section: Background and Scopementioning
confidence: 99%
“…Further, curated databases may collaborate more closely with field experts, in order to preserve the multi-faceted neuroanatomical knowledge acquired in many experimental labs over several decades (where knowledge is currently threatened by the upcoming retirement of many of the "traditional" anatomists), or new experimental efforts may be started for the systematic, "industrial" brain connectivity gathering in rodent models (Bohland et al, 2009;Zakiewicz et al, 2011).…”
Section: Applied Connectomics: Network Analysis and Modelingmentioning
confidence: 99%